A SOCIAL REALIST PERSPECTIVE OF CHALLENGES FACING EDUCATORS IN IMPLEMENTING THE REVISED CURRICULUM IN OMPUNDJA CIRCUIT IN NAMIBIA - Josua , Lukas; Auala, Rehabeam; Miranda, Helena (African Journal of Education and Practice, 2022)
Purpose: This article explores the challenges experienced by Namibian public schools' educators when implementing the revised curriculum in Ompundja Circuit and suggests how the challenges can be addressed. Methodology: A qualitative design using a semi-structured interview guide was employed to collect data from five purposively sampled principals. About 45-minute long face-to-face interviews were conducted with each of the principals. The data collected through interviews were transcribed and read several times to make meaning from the volume data. After reading all the interview transcripts, various codes were assigned to themes using a priori or pre-existing coding. The interpretation was derived from the transcribed responses of participants. Findings: The study found that there are structural, cultural and agential constrains that could hinder the successful management and implementation of the revised curriculum in Namibian public schools in Ompundja Circuit. These challenges may derail the purpose of instructional leadership, which seeks to improve learners' academic performance country-wide. The study proposed some enabling mechanisms to address the identified challenges. Unique contribution to theory, practice and policy: This study made a set of recommendations such as: training of educators on curriculum implementation should be conducted regularly; stakeholders should be provided with the necessary instructional materials and teachers are encouraged to use alternative teaching and learning resources. Further, it is recommended that the teacher-learner ratio policy should be morphed to respond to contexts. It is also recommended that schools should mobilise monetary or in-kind assistance from stakeholders, including parents. The current policy that prevents schools from soliciting school development funds from parents and denies teachers the opportunities to use the Universal Primary Education funds for educational excursions should be revised. It is also recommended that schools should be provided with the necessary physical infrastructures. Finally, it is recommended that teachers should be involved in every curriculum development process and decision making thereof.